2006
DOI: 10.1097/00124509-200606000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Memory, Attention, and Executive Functions Before and After Sine and Pulse Wave Electroconvulsive Therapies for Treatment-Resistant Major Depression

Abstract: Anterograde memory improved to a statistically significant or nonsignificant degree at 1 week post-ECT in comparison with pre-ECT regardless of waveforms. Attention/executive functions tended to deteriorate with sine wave ECT but improved with pulse wave ECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
2
19
2
Order By: Relevance
“…41 58 Other studies, however, have found no change immediately after a course of ECT. For example, Dubovsky et al 41 found no change in psychomotor speed as measured by TMT part A or Digit Symbol at the conclusion of a course of either RUL or BL ECT (analyzed together).…”
Section: Information Processing Speed/reaction Timementioning
confidence: 96%
See 1 more Smart Citation
“…41 58 Other studies, however, have found no change immediately after a course of ECT. For example, Dubovsky et al 41 found no change in psychomotor speed as measured by TMT part A or Digit Symbol at the conclusion of a course of either RUL or BL ECT (analyzed together).…”
Section: Information Processing Speed/reaction Timementioning
confidence: 96%
“…41,58,59 For instance, in a recent study Tsourtos et al 57 found that depressed patients performed significantly slower after a course of ECT (BL and RUL electrode placement) on an inspection time task than at baseline; performance improved significantly by 4-to 6-week follow-up. By contrast, the performances for the control group continued to improve (ie, quicken) throughout the study.…”
Section: Information Processing Speed/reaction Timementioning
confidence: 99%
“…While some recent studies have shown that ECT adversely effects cognitive and memory function (1517) specifically within the first 7 to 8 days (18), others have reported that cognition returns to baseline (19) or even improves (20, 21) following treatment. Cognitive measurements included autobiographical (episodic) and working memory, information processing, and executive function.…”
Section: Introductionmentioning
confidence: 99%
“…6 A few studies focused on the impact of sine and pulse waveforms on anterograde memory and other cognitive functions. 7 Other side effects of ECT include headache, muscle aches, nausea, and fatigue. 8Y11 Electroencephalogram measures of ECT treatment were modestly associated with clinical outcome, greater ictal power, delta coherence, and postictal suppression predictors of greater therapeutic benefit.…”
mentioning
confidence: 99%